1991
DOI: 10.1159/000125777
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro Studies on the Opioidergic Control of the Secretion of Gonadotrophin-Releasing Hormone and Luteinizing Hormone in Sexually Immature and Adult Male Rats

Abstract: In vivo and in vitro methods have been used to compare the effects of opioid receptor blockade on the functional activity of the hypothalamo-pituitary-gonadal axis in adult (200 g) and sexually immature (50 g) male rats. In the adult, a single injection of the µ-receptor antagonist, naloxone (500 µg/100 g body weight, s.c), produced hypersecretions of luteinizing hormone (LH) and testosterone. Maximal serum concentrations of the two hormones were attained within 20 and 60 min respectively. In contrast, neither… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Our in vitro studies were based on a well-characterized hypothalamic preparation which has been used widely in studies on the mechanismscontrolling the release of CRF-41 and other releasing hormones [12,13,49], With regard to CRF-41. the data presented here confirm previous reports from our own [12,13] and other [50] laboratories that IL-la, IL-lp, IL-6 and IL-8 cause significant in creases in peptide release which are generally more pro nounced in tissue derived from adrenalectomized than intact rats [ 12. 13] and which are antagonized by preincubation of the tissue with dexamethasone within the time frame of the early-delayed feedback response [ 13].…”
Section: Discussionmentioning
confidence: 99%
“…Our in vitro studies were based on a well-characterized hypothalamic preparation which has been used widely in studies on the mechanismscontrolling the release of CRF-41 and other releasing hormones [12,13,49], With regard to CRF-41. the data presented here confirm previous reports from our own [12,13] and other [50] laboratories that IL-la, IL-lp, IL-6 and IL-8 cause significant in creases in peptide release which are generally more pro nounced in tissue derived from adrenalectomized than intact rats [ 12. 13] and which are antagonized by preincubation of the tissue with dexamethasone within the time frame of the early-delayed feedback response [ 13].…”
Section: Discussionmentioning
confidence: 99%
“…First, the phenomenon be a stress-induced response to weaning, mediated by endogenous opiates that are known to affect GnRH release and pulsatility (55)(56)(57). Second, the increased GnRH gene transcription may be a temporal phenomenon dependent on a number of preceding developmental events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have also shown that m-and k-opioid agonists not only reduce LH release at 1800 h, but also alter monoamine levels at 1430 h on the afternoon of pro-oestrus (9,11,(28)(29)(30). The findings on the role of d-receptors on LH release are conflicting (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…]enkephalin; DPDPE) was seen to inhibit LH release in females (15), but a specific d-antagonist (ICI 154, 129) did not affect LH levels in males (16). The d-receptors have a more restricted distribution than the m-and k-receptors in the brain, and their density has been described as low to moderate in the rat hypothalamus with the highest levels located in the medial preoptic area (MPOA) and suprachiasmatic nucleus (SCN) (17,18).…”
Section: Introductionmentioning
confidence: 99%